How to Write for Your Website - Sarah Graddy; Tracy Irani (EDIS, 2006)
AEC-378, a 4-page fact sheet by Sarah Graddy and Tracy Irani, provides guidelines for effectively delivering information to extension clientele on the Web. Includes list of useful Web-based resources. Published by the UF Department of Agricultural Education and Communication, August 2006.